The Students’ Knowledge, Attitudes, and Behavior in Learning History at Pesantren Buya Hamka - Indra, Ristapawa; Kustati, Martin (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2020)
This study aims to determine the implementation stage of history learning process for students at the Pesantren Buya Hamka; the stages of knowledge, attitudes, and behavior of students regarding nationalism and patriotism; and the correlation of leadership variables, school climate, teacher performance, and pesantren culture to history learning and also to students’ knowledge, attitudes, and behavior regarding nationalism and patriotism. This study also aims to find out the significant influence of historical learning variables on knowledge, knowledge variables on attitudes and attitudes on students’ behavior. This study combines survey research quantitative approach with descriptive, correlation, and regression methods. The results show there is a significant correlation between independent variables with historical learning variables and student knowledge variables about nationalism and patriotism. Meanwhile, there is no significant correlation between independent variables and student behavior variables. The results also show only the history of learning variables among the five independent variables that significantly influence the knowledge of nationalism and student patriotism. Student knowledge variables about nationalism and patriotism partially also affect changes in student attitudes, while changes in student attitudes do not affect linearly on changes in student behavior. Penelitian ini bertujuan untuk mengetahui tahap pelaksanaan pembelajaran sejarah siswa di Pesantren Buya Hamka Kota Padang; tahap pengetahuan, sikap dan perilaku siswa berkenaan dengan nasionalisme dan patriotisme melalui pembelajaran sejarah; dan korelasi variabel kepemimpinan, iklim sekolah, kinerja guru dan kultur Pesantren terhadap pembelajaran sejarah dan juga terhadap pengetahuan, sikap dan perilaku siswa berkenaan dengan nasionalisme dan patriotisme. Kemudian, penelitian ini juga bertujuan untuk mengidentifikasi pengaruh signifikan variabel pembelajaran sejarah terhadap pengetahuan, pengaruh variabel pengetahuan terhadap sikap dan pengaruh sikap terhadap perilaku siswa. Penelitian ini perpaduan penelitian survey dengan pendekatan kuantitatif dengan metode deskriptif, korelasi dan regresi. Hasil penelitian menunjukkan terdapat korelasi signifikan antara variabel indenpendent dengan variabel pembelajaran sejarah dan variabel pengetahuan siswa tentang nasionalisme dan patriotisme. Sementara itu, tidak terdapat korelasi yang signifikan antara variabel independen dengan variabel perilaku siswa. Berikutnya hasil analisis menunjukkan hanya variabel pembelajaran sejarah diantara lima variabel indenpenden yang berpengaruh secara signifikan terhadap pengetahuan nasionalisme dan patriotisme siswa. Variabel pengetahuan siswa tentang nasionalisme dan patriotisme secara parsial juga berpengaruh terhadap perubahan sikap siswa, sementara perubahan sikap siswa tidak berpengaruh secara linear terhadap perubahan perilaku siswa.